Axially displaced elliptical reflector antenna design with a switchable feeder for ultra-wide band applications - Kenan, Ahmet Keskin; Caliskan, Alper (INST ENGINEERING TECHNOLOGY-IET, 2018)
This study presents a novel compact high gain dual reflector antenna design with a switchable feeder for ultra-wide band (UWB) applications. The design comprises a main parabola, a replaceable feeder antenna that is chosen depending on the requirements in a given situation, and an axially displaced elliptical sub-reflector. The functioning of two different feeder antennas with manual switching option, the partly dielectric loaded K-Vivaldi and double-ridged horn (RH), is discussed in this research study. When the K-Vivaldi is employed, the dual reflector antenna is more appropriate for impulse radiation with 33:1 operational bandwidth, ranging from 600MHz to 20GHz. The double-RH feeder antenna displays more efficiency than the K-Vivaldi one; however, the bandwidth in this case goes down to 12:1, ranging from 1.6 to 20GHz. The sub-reflector, situated inside the main parabola aperture with onset type of feeders, reduces the depth of the structure to 16cm. The antenna dimensions are 60cmx60cmx16cm. Experiments have shown that the designed antennas display good efficiency and high gain performances in UWB operations.
Keywords: microwave antennas; ultra wideband communication; ultra wideband antennas; horn antennas; antenna radiation patterns; broadband antennas; reflector antenna feeds; dielectric devices; replaceable feeder antenna; manual switching option; partly dielectric loaded K-Vivaldi; double-ridged horn; double-RH feeder antenna; main parabola aperture; antenna dimensions; switchable feeder; ultra-wide band applications; novel compact high gain dual reflector antenna design; operational bandwidth; axially displaced elliptical reflector antenna design; axially displaced elliptical subreflector; impulse radiation; frequency 600 MHz to 20 GHz; frequency 1; 6 GHz to 20 GHz; MONOPOLE ANTENNA; SIMULATION; Engineering; Telecommunications